Development of Gamification-Based Story Learning E-Book to Improve Simple Sentence Writing Skills in Grade Two Elementrary School Students - Widia Situmeang; Nugraheti Sismulyasih SB (Universitas Pendidikan Mandalika, 2026)
This study aims to design, assess the feasibility, and evaluate the effectiveness of a gamification-based e-book for story learning to enhance simple sentence writing skills among second-grade students at SDN Tawangmas 01 Semarang. The study employed a Research and Development (R&D) approach, adapting the Borg and Gall model into eight stages. The research instruments included validation sheets for media and material experts, teacher and student questionnaires, and pretest–posttest writing assessments to measure students’ simple sentence writing skills. The data were analyzed using descriptive statistics to determine feasibility and user responses, while effectiveness was examined using a paired-samples t-test and normalized gain (N-gain) analysis. The findings indicate that the gamification-based e-book achieved high feasibility ratings, with scores of 93.75% from media experts and 96.24% from subject matter experts. Positive responses were also obtained from teachers (81.53%) and students (94.44%). Furthermore, the e-book was effective in improving students’ simple sentence writing skills, as evidenced by a statistically significant result (p < 0.05) and an increase in mean scores from 48.77 (pretest) to 77.72 (posttest). The N-gain value of 0.5277 (52.77%) falls within the moderate category. In conclusion, the gamification-based story learning e-book represents an innovative instructional medium that supports Indonesian language learning and enhances elementary students’ foundational literacy skills.